Pengenalan dan Penerapan User Interface and User Experience Design for Beginners - Wardhanie, Ayouvi Poerna; Rahmawati, Endra (Batara Wisnu : Indonesian Journal of Community Services, 2022)
One indicator of the success of a platform so as it can attract customers to visit is a user-friendly and creative application design, in the area of information technology known as User Interface and User Experience. Therefore, to improve the ability, both intellectually and practically, a community service activity is carried out, especially for the younger generation in the form of introducing and implementing UI/UX designs for beginners so that they can compete with today's business and technology world.This activity, which is packaged in the form of a webinar, focuses on understanding the basics of UI/UX design and its methodology as well as how to apply the tools, namely Figma, to design a website. Participants in this workshop amounted to 166 people spread across various parts of Indonesia, with an online learning method using Zoom for two hours. As a result of this activity, participants were able to follow the material given by the two speakers well, but in terms of time efficiency, there were delays due to technical problems. Participants' input for the material in the next activity is more focused on graphic design, coding, big data and cyber security